Pengaruh Budaya Organisasi, Kepemimpinan, Kemampuan Kognitif, Dan Motivasi Kerja Terhadap Kinerja Pegawai Di DISKOMINFO SUMUT - Rosmanidar Sinaga; Zainuddin Zainuddin; Nasrun Nasrun; Akmaluddin Akmaluddin (Universitas Negeri Medan, 2021)
The purpose of this study was to find out and examine : (1) the employee performance model built on associative causal relationships between exogenous variables and endogenous variables,, (2) the effect of organizational culture on job motivation, (3) the effect of leadership on job motivation, (4) the effect of cognitive ability on job motivation, (5) the effect of organizational culture on employee performance, (6) the effect of leadership on employee performance (7) the effect of cognitive ability on employee performance, and (8) the effect of job motivation on employee performance. This research was conducted at Diskominfo office in North Sumatera by involving 139 employee as respondents. Data collection is done by using a questionnaire with five answer choices. The sampling technique were used proportional random sampling. The instruments were used first tried out to respondent outside the sample to obtain validity and reliability Instruments. Validity test uses Product Moment correlation, while to test its reliability with Alpha formula from Cronbach. Before testing the hypothesis, especially before the test is calculated, the requirements of the analysis include: normality data test and regression linearity test. The results showed (1) Obtained the employee performance model, (2) there is positive direct effect of organizational culture to job motivation, (3) there is positive direct effect of leadership to job motivation, (4) there is positive direct effect of cognitive ability to job motivation, (5) there is positive direct effect of organizational culture to employee performance, (6) there is positive direct effect of leadership to employee performance, (7) there is positive direct effect of cognitive ability to employee performance, and (8) there is positive direct effect of job motivation to employee performance. Based on the acceptance of the research hypothesis, it is found a fixed model that describes the structure of causal relationships between organizational culture, leadership, cognitive ability, job motivation and employee performance at Diskominfo office in North Sumatera.